POINT EXPLOSION WITHIN A CAVITY WITH A POWER-LAW DENSITY DISTRIBUTION - Martiushov, V. V.; Silich, S. A. (Одеські астрономічні публікації, 2017)
An exact analytic solution based on the Kompaneets approximation is found for a shock wave expansion from a point explosion within a preexisting interstellar gas cavity with a power-law gas density distribution. An obvious shock deviation from the spherical symmetry is revealed for the off-center explosion. It is assumed this may give a reason for the complex morphology that is observed in some supernova remnants.